The Role of Parents in Cultivating the Religious Character of Elementary School Age Children During the Covid-19 Pandemic: Peran Orang Tua Dalam Menumbuhkan Karakter Religius Anak Usia Sekolah Dasar Pada Masa Pandemi Covid-19 - Novia Cahya Istiana; Feri Tirtoni (Academia Open, 2022)
This study aims to find out what the role of parents is in cultivating the religious character of elementary school age children during the COVID-19 pandemic and to find out what the religious character of grade 4A students at SDN JEPARA 1/90 is like. This research uses descriptive qualitative research with case studies. This study uses interview techniques, questionnaires, and documentation. The subjects studied in this study were 5 guardians and 5 students in grade 4A. The results of this study are parents act as role models and motivators for children, and the religious character of grade 4A students at SDN JEPARA 1/90 has shown indicators of obedience to Allah SWT, sincerity, responsibility and tolerance.